Assessing Integrated Territorial Development Strategies - Medeiros, E. (ESPON Scientific Conference 2018, 2018)
Integrated tTerritorial iInvestment (ITI) is a new policy tool for use during the European Structural and Investment Funds (ESIF) programming period, with the main goal of which is to “make it easier to run territorial strategies that need funding from different sources. ITI also promotes a more local or ‘place-based’ form of policy making” (EC, 2015: 6). This more integrated approach to policy intervention entails more collaborative models of governance, and covers different territorial scales. In the present EU Cohesion Policy programming period, at the urban level, the European Commission (EC) has been supportsing the implementation of Integrated Sustainable Urban Development StrategiesISUDSs across hundreds of European cities, as a somewhat novel policy tool for uUrban dDevelopment. Conceptually, the paper proposes a framework for the assessment of the territorial approach that is based on six vectors (integration of policy areas, impact of operations, planning horizon, territorial targeting, inclusiveness and strength of the monitoring framework). The article focuses on the case of Portugal, which has offereds a wide set of EU- financed integrated urban development integrated strategies, since 1994 (under the URBAN Urban CI, PolisOLIS and Portuguese sustainable urban development strategies (SUDSs)), in the major urban agglomerations.